SEASONAL BEHAVIOUR OF KERATINOPHILIC FUNGI ISOLATED FROM PARKS SOIL IN MILAN (Boletín Micológico, 2005)
Soil samples collected from 10 parks in Milan were examined for the presence of keratinophilic fungi by the Orr’s hair baiting technique. The organisms isolated and their frequency were as follows: Arthroderma uncinatum and its anamorph Keratinomyces ajelloi were dominantand recovered from 22.5% - 43.7% and 40% - 50% of the soil samples collected in summer and winter respectively. Myceliophthora vellerea was isolated in 31.2% of the samples, particularly in winter, Microsporum gypseum in winter (20%) and Trichophyton terrestre (10%) in summer.Chrysosporium keratinophilum (16.2% in summer and 18.7% in winter) C. indicum (15% s- 23.7% w), C. pannicola (5% s - 37% w). Aphanoascus fulvescens was isolated in summer (23.7%). Among the cycloheximide-resistant keratinophilic fungi Alternaria alternata (27.5% s – 33.7% w), Paecilomyces lilacinus (26.2% s - 18.7% w) and Acremonium strictum (8.7% s - 20% w) also were observed. The distribution of the different species is discussed.